Bottom-Up Control of Macrobenthic Communities in a Guanotrophic Coastal System - Signa, Geraldina (PLoS One, 2015)
Soft bottom macrobenthic communities were studied seasonally in three coastal ponds (Marinello ponds, Italy) at increasing distances from a gull (Larus michahellis) colony to investigate the effect of seabird-induced eutrophication (i.e. guanotrophication) on macrobenthic fauna. We hypothesized that enhanced nutrient concentration and organic load caused by guano input significantly alter the trophic and sedimentological condition of ponds, affecting benthic fauna through a bottom-up control. The influence of a set of environmental features on macrobenthic assemblages was also tested. Overall, the lowest macrobenthic abundances and functional group diversity were found in deeper sites, especially in the pond characterised by severe guanotrophication, where the higher disturbance resulted in a decline in suspension feeders and carnivores in favour of deposit feeders. An increase in opportunistic/tolerant taxa (e.g. chironomid larvae and paraonids) and totally azoic sediments were also found as an effect of the harshest environmental conditions, resulting in a very poor ecological status. We conclude that macrobenthic assemblages of the Marinello coastal system display high spatial variability due to a synergistic effect of trophic status and the geomorphological features of the ponds. The macrobenthic response to guanotrophication, which was a clear decrease in abundance, diversity and trophic functional groups, was associated with the typical response to severe eutrophication, magnified by the geomorphological features.